Happiness based on religion case of Christianity in Thailand: national survey - Klangrit, Suriya (Journal of spirituality in mental health, 2026)
This study investigates the relationship between happiness and Christianity in Thailand, focusing on the roles of religiosity and religious activities. Using a quantitative approach, secondary data from a national survey of 505 Thai Christians were analyzed. An independent samples t-test was conducted to test the hypotheses. The results revealed two key findings: (1) Religiosity did not significantly contribute to happiness among Thai Christians. Specifically, neither church attendance nor engagement in Christian prayers had a statistically significant impact on happiness levels, suggesting that religiosity may not play a substantial role in determining happiness in this context. (2) Religious activities yielded mixed results. While certain activities, such as teaching problem-solving skills for life and practicing religious teachings, had a significant positive impact on happiness, other aspects such as financial contributions to the church, charity donations, the perceived importance of religious teachings for daily living, belief in religious doctrines, and overall religious activity did not show significant differences in happiness levels. These findings highlight the need to reevaluate the factors influencing happiness among Christians in Thailand and suggest that broader, non-religious influences may be at play. The study offers valuable insights for policymakers, religious leaders, and mental health professionals seeking to design culturally sensitive interventions to enhance happiness within Christian communities in Thailand.